The little data book on external debt. (Little data book on external debt, 2009)
The Little Data Book on External Debt provides a quick reference for users interested in external debt stocks and flows, major economic aggregates, key debt ratios, and the currency composition of long-term debt for all countries reporting through the Debtor Reporting system. A pocket edition of the Global Development Finance 2009, Volume II: Summary and Country Tables, it contains statistical tables for 135 countries as well as summary tables for regional and income groups.